Leisure activity engagement as a predictor for quality of life in community-Dwelling older adults - Valiollah Marufkhani; Fatemeh Mohammadi; Monirsadat Mirzadeh; Kelly-Ann Allen; Seyedeh Ameneh Motalebi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Participation in leisure activities is greatly associated with the health and well-being of older adults. This study investigated the role of leisure activities in predicting the quality of life of community-dwelling older adults. Methods: In this descriptive and cross-sectional study, 141 older adults were selected by cluster sampling method from public places. Data were collected through demographic characteristics, leisure time activities, and Lipad QoL questionnaires. The questionnaires were completed through face-to-face interviews. A regression model was used for data analysis. Results: The mean age of older adult participants was 70.36 years (standard deviation = 8.99; range: 60-100 years) and 63.8% were male. The results also showed a low level of leisure time engagement and high level of QoL among older adults. The results of the current study indicated that education level and leisure time activity engagement were associated with a better QoL. Conclusion: According to the results of this study, engagement in leisure activities is related to improvements in the QoL of community-dwelling older adults. It is recommended that policymakers and families plan for and implement leisure time activities for older adults.